46‐3: High Contrast Ratio Electrochromic Light Shutter Device for Optical See‐through Type Head Mounted Display. Issue 1 (May 2017) - Park, Jin Hwan; Kim, Yong Cheol; Ko, Ik Jang; Kim, Gyeong Woo; Kwon, Jang Hyuk
Abstract : Transmittance adjustable new electrochromic device (ECD) for optical see‐through type head mounted display is reported to provide good visibility by reducing external light intensity in the bright environment. Significantly improved ambient contrast ratio of 7.4 times under 400 lux bright condition is observed by this ECD.